Midlife memory improvement predicts preservation of hippocampal volume in old age - Borghesani, Paul R. (2010)
This study examines whether midlife change in episodic memory predicts hippocampal volume in old-age. From the Seattle Longitudinal Study we retrospectively identified 84 healthy, cognitively normal individuals, age 52 to 87, whose episodic memory had reliably declined (n=33), improved (n=28) or remained stable (n=23) over a 14 year period in midlife (age 43–63). Midlife memory improvement was associated with 13% larger hippocampal volume (p < 0.01) in old-age (age 66–87), compared to old-age individuals whose midlife episodic memory had either declined or remained stable during midlife. Midlife memory change did not predict total hippocampal volume for those currently in late middle-age (age 52–65). The pattern of findings was not modified by gender, apolipoprotein ε4 status, education or current memory performance. Change in midlife memory scores over 14 years, but not any single assessment, predicted hippocampal volumes in old age, emphasizing the importance of longitudinal data in examining brain-cognition relationships. These findings suggest that improvement in memory in midlife is associated with sparing of hippocampal volume in later life.